A Copa do Mundo de 2014 e a cidade: impacto dos megaeventos na política urbana - Mariana Grilli Belinotte (2021)
What is the impact of megaevents in the cities? Specifically, what were the impacts of the FIFA World Cup 2014 in Brazil regarding urban competition, norms flexibilization, political participation and investment distribution? The methodology chosen to answer these questions was the juridical-comprehensive method. The technics used were the documental analysis and the bibliographical revision. Laws and newspaper articles - from Folha de São Paulo and O Estado de São Paulo - were used for the documental analysis; works from the Law, Geography, History and Public Administration areas were used in the bibliographical revision. The data shows that the megaevents have the capability of accelerating processes of unequal distribution of investments and space privatization and its reformulation aimed to fulfilling the specific needs of transnational actors, in detriment of citizens and residents, a phenomena which could also be seen in the 2014 Cup.